Outcrossing rate and genetic variability in mexican race avocado - Sánchez González, Enrique I.; Gutiérrez Díez, Adriana; Mayek Pérez, Netzahualcóyotl (American Society for Horticultural Science, 2020)
The blooming behavior of the avocado Persea americana Mill. is a sophisticated mechanism that prevents effective self-pollination, enables close pollination, and encourages cross-pollination. However, there is no information on outcrossing rate among Mexican race avocado genotypes (P. americana var. drymifolia Schltdl. & Cham.). Therefore, the objective of this study was to assess the outcrossing rate and genetic variability in progenies of Mexican race avocado genotypes by simple sequence repeat (SSR) and intersimple sequence repeat (ISSR) markers. SSR marker analysis showed a considerable genetic differentiation among avocado families [total expected heterozygosity (He) = 0.540], whereas the total heterozygosity value observed (Ho = 0.098) showed the presence of genetic structure per family. The total Nei’s unbiased average heterozygosity (nHe) value found with ISSR markers was 0.482. The results of the analysis of molecular variance (AMOVA) combining both type of markers showed that genetic variation within avocado families was 58.6%, and among families was 41.6% (P < 0.0001). The outcrossing population rate in P. americana var. drymifolia was 0.774 ± 0.091 (SD), and the ‘Criollo 3’ and ‘Platano Temprano’ families showed the lowest (–0.083 ± 0.031) and highest (0.814 ± 0.060) outcrossing rates, respectively. Variability in outcrossing rate depends on many factors, including edaphoclimatic, agronomic, and genetic, and needs to be considered to define strategies for the conservation and genetic improvement of outstanding native genotypes. SSR and ISSR markers are useful for estimating genetic variability within and among families of avocado, as well as for determining the outcrossing rates among closely related individuals and with a rather small sample size.